Public knowledge, attitudes and practices towards COVID-19 - Nur Alvira Pascawati; Tri Baskoro Tunggul Satoto (Intelektual Pustaka Media Utama, 2020)
In an effort to control the COVID-19 outbreak in Indonesia, the government implemented rules such as clean and healthy living behavior by all components of public, isolation, and early detection. Community knowledge, attitudes and practices (KAP) towards COVID-19 play an important role in determining the readiness of the community in accepting policies in the form of behavior change from the health authority. The aim of this study is to determine the KAP toward COVID-19 in Yogyakarta, Indonesia. A cross-sectional online survey of 155 householders was conducted between 04 May 2020 and 18 May 2020. Descriptive statistics, t-tests and one-way analysis of variance were conducted. Most public have understood about causes symptoms, mode transmission, high risk groups, isolation and quarantine, and proper use of disinfectants but people have not been able to distinguish between how to increase immunity and how to prevent COVID-19 transmission. The public has a positive belief that the government will succeed in controlling and managing a health crisis. Public behavior to prevent COVID-19 transmission is good, except the use of disinfectants and stop smoking or prohibiting family members from smoking. Differences in public knowledge, attitudes and practices towards COVID-19 occur in different gender and occupational groups.